Implementation of English Word Repair to Improve EFL Speaking Skills in Private Lessons (Informal Conversation) - Ariyanti, Desita Agustina; Laila, Malikatul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: In language learning, the word repair is a pedagogical approach whereby the teacher repeats the word uttered by the student and offers a corrective or interpretive response to foster comprehension of the word in question, whether in terms of its meaning or pronunciation. This study aims to gain a deeper understanding of the efficacy of word repair as a tool for developing students’ pronunciation skills in private teaching contexts. Methodology: This study adopted a qualitative classroom action approach, using observation and note-taking as data collection techniques. In addition, interviews were also used to record data collection and tests where students were asked to pronounce the prescribed word correctly. With the data collected from 4 students with different levels, it will add accuracy related to this study. Results: The findings of this study indicate that consistent vocabulary repair, coupled with constructive feedback, is a practical approach to enhance students’ speaking fluency, pronunciation, and confidence in using English. This is evidenced by the observed improvement in students’ scores before and after the implementation of word repair. Applications/Originality/Value: This research is useful for providing an understanding of what the remedial learning method will support in speaking in addition to speaking itself. It will also increase the functionality of the approach so that it does not have only one purpose. This research is certainly useful for teachers to reference learning in speaking skills and for students to understand one way to improve speaking.